2004
DOI: 10.1080/1350485042000203742
|View full text |Cite
|
Sign up to set email alerts
|

More on the estimation of the human capital depreciation rate

Abstract: This study formulates an alternative empirical model to that of Groot (Applied Economics Letters, 5, 535-8, 1998) to estimate the rate of depreciation of human capital, in which the post-schooling investment and the difference between the potential and the observed earnings of the individuals are taken into account. As an illustration, the model has been estimated for a sample of Spanish men and women. The results show depreciation rates of human capital of around 1-1.5% per year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 9 publications
4
27
0
1
Order By: Relevance
“…others reported in the literature, especially with those obtained by Hansen (1993) and Altig et al (2001). The estimate of δ h = 0.011 is reasonable (Arrazola andde Hevia (2004), Browning, Hansen, andHeckman (1999)), and the estimate of ψ = 0.67 is just in the middle of the range reported in Browning, Hansen, and Heckman (1999). …”
Section: Individual Productivity Profilessupporting
confidence: 62%
“…others reported in the literature, especially with those obtained by Hansen (1993) and Altig et al (2001). The estimate of δ h = 0.011 is reasonable (Arrazola andde Hevia (2004), Browning, Hansen, andHeckman (1999)), and the estimate of ψ = 0.67 is just in the middle of the range reported in Browning, Hansen, and Heckman (1999). …”
Section: Individual Productivity Profilessupporting
confidence: 62%
“…The learning literature agrees that experience depreciates over time: that is, experience gained recently is more important for success than experience gained longer ago (e.g., Arrazola and Hevia 2004;Arthur and Huntley 2005;Boone et al 2008;Darr et al 1995;Groot 1998;Madsen and Desai 2010). However, consensus is lacking regarding the depreciation rate of experience, with depreciation rates being reported that range from 67 to 96 % per month Benkard 2000;Epple et al 1996) to 11-17 % per year (Groot 1998).…”
Section: The Datamentioning
confidence: 92%
“…However, apart from that, most studies focus on wages. While some try to measure the rate of depreciation exactly, such as Arrazola and de Hevia (2004) or Groot (1998), others focus more on the detection of vintage effects or depreciation in general (Neuman & Weis 1995, Weiss & Lillard 1978.…”
Section: Literature and Theorymentioning
confidence: 99%